SakeraHerbDB Proposing an Integrated Indonesian Traditional Herbal Medicine Database IITHMDB for Madura Islands Herbs - Muhammad Yusuf; M Kautsar Sophan; Aang Kisnu Darmawan; Devie Rosa Anamisa; Budi Dwi Satoto; Nurwahyu Alamsyah (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Indonesian Traditional Herbal Medicine Databases are crucial for maintaining indigenous knowledge bridging traditional medicine with modern healthcare and promoting evidencebased research These databases help identify therapeutic compounds and modernize traditional medicine practices However Traditional herbal medicine databases in Indonesia need to be improved in dissemination documentation safety quality and research on COVID19 This research aims to create SakeraHerbDB an integrated Indonesian Traditional Herbal Medicine Database for Madura Island botanicals The database will integrate traditional and modern medicine by combining traditional knowledge scientific facts and ecological factors The study reviews Indonesian traditional herbal medicine literature focusing on Madura Island botanicals Ethnobotanical research local knowledge holders and herbal medicine practitioners will collect data A structured database and data entry processes will be created for accuracy and consistency The database will have an easytouse interface This study produced six submissions for the Integrated Indonesian Traditional Herbal Medicine Database IITHMDB for Madura Islands herbs Use Case Diagram Database Attribute System Architecture Decision Tree Flowchart SakeraHerbDB Webbased application and Searching SakeraHerbDB with Decision Tree algorithm This research improves traditional knowledge integrates traditional and contemporary medicine advances herbal medicine research empowers local populations and promotes sustainable resource management SakeraHerbDB will unify data fill knowledge gaps and promote interdisciplinary collaboration The database will benefit healthcare workers researchers policymakers and innovators